Modified thickening agent and gelled acid system containing same
Modified thickener is prepared by step-by-step reverse phase emulsion polymerization to form a high-temperature gelling acid system, which solves the problem of the existing gelling acid dropping at high temperatures, and achieves stable viscosity and ease at high temperatures corrosion performance.
Patent Information
- Application Number
- CN202310942818.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-14
AI Technical Summary
The viscosity of the existing gelled acid drops rapidly under high temperature conditions and cannot meet the slow performance requirements of deep acid pressure.
Modified thickening agents are prepared by step-by-step reverse phase emulsion polymerization copolymerization, including acrylamide, 2-acrylamide-2-methylpropanesulfonic acid and N-(2-(allylbromoamino)-2- Phenethyl)heptanamide and other materials form a gelling acid system that is resistant to high temperature.
It improves the viscosity holding ability and corrosion inhibitory performance of the gelling acid system at high temperatures, can effectively reduce corrosion to the wellbore and downhole equipment, and is suitable for reservoir conditions of 80-230℃.
Smart Images

Figure CN119431806A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of oilfield chemical additives, and particularly relates to a modified thickener and a gelled acid system containing the modified thickener. Background Art
[0002] As exploration and development continue to deepen, the proportion of high-temperature carbonate reservoirs continues to rise. The success of carbonate reservoir fracturing and acidizing mainly depends on two factors: one is the effective length of the final acid fracturing fracture, and the other is the conductivity of the acid-etched fracture after acid fracturing. At high temperatures, the acid-rock reaction speed is fast, and the effective action distance of the acid is short. Conventional acid cannot achieve the purpose of deep acid fracturing. It is urgent to develop a new acid system to meet the requirements of acid fracturing and production increase. Gelled acid is a commonly used acid system in carbonate reservoir development operations. The acid has the advantages of good retarding properties and small filtration loss. However, under high temperature conditions, the existing gelled acid cannot achieve the ideal acidizing effect. The viscosity of the gelled acid decreases rapidly at high temperatures, and the retarding performance cannot meet the requirements of deep acid fracturing. Therefore, this requires the acid system to have excellent retarding properties at high temperatures, and at the same time, a suitable process should be selected to cooperate with the developed retarding acid liquid with better temperature resistance and retarding properties. Summary of the invention
[0003] In view of the above problems, the present invention provides a modified thickener and a gelling acid system comprising the same.
[0004] The object of the present invention is to provide a modified thickener, which is prepared by the following steps:
[0005] Acrylamide, 2-acrylamido-2-methylpropanesulfonic acid and deionized water are prepared into a first aqueous phase solution, kerosene and a first emulsifier are added under nitrogen atmosphere and stirring, and an initiator is added after stirring and mixing once, and stirring and mixing a second time to obtain a first mixed solution, and the obtained first mixed solution is heated to react to obtain a polymer A;
[0006] Acrylamide, N,N'-dimethylacrylamide and deionized water are prepared into a second aqueous phase solution, kerosene and a second emulsifier are added under nitrogen atmosphere and stirring, and the mixture is stirred and mixed three times, and then an initiator is added, and the mixture is stirred and mixed four times to obtain a second mixed solution, and the obtained second mixed solution is heated to react to obtain polymer B;
[0007] Acrylamide, N-(2-(allylbromoamino)-2-phenylethyl)heptylamide and deionized water are prepared into a third aqueous phase solution, kerosene and a third emulsifier are added under nitrogen atmosphere and stirring, and after stirring and mixing for five times, an initiator is added and stirred for six times to obtain a third mixed solution, and the obtained third mixed solution is heated for reaction to obtain a polymer C;
[0008] After polymer A, polymer B and polymer C are mixed, they are heated to the reaction temperature under nitrogen atmosphere and stirring, and an initiator is added. The stirring reaction is continued to obtain a product, which is polymer D. After post-treatment, a modified thickener is obtained.
[0009] Furthermore, in the preparation process of the polymer A, the mass ratio of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, deionized water, kerosene, the first emulsifier, and the initiator is 1-1.5:1-1.5:7-7.5:4-4.5:0.1-0.5:0.01-0.3.
[0010] The mass ratio of acrylamide, 2-acrylamido-2-methylpropane sulfonic acid, deionized water, kerosene, the first emulsifier and the initiator can also be one of 1:1:7:4:0.2:0.1, 1.5:1:7.5:4.5:0.3:0.05, 1.5:1:7:4:0.1:0.1, 1:1:7:4.5:0.3:0.01 and 1.5:1.5:7.5:4:0.3:0.2.
[0011] Furthermore, the first emulsifier is any one of oil-in-water emulsifiers, such as Span20, Span60, Span80, Tween80, etc.
[0012] Furthermore, the initiator is one of the azo initiators, such as azobisisobutyronitrile, azobisisoheptanenitrile, azobisisobutyramidine hydrochloride, azobisisobutylimidazoline hydrochloride, etc.
[0013] Furthermore, the first stirring and mixing time is 30 to 60 minutes, the second stirring and mixing time is 20 to 40 minutes, the reaction temperature of the first mixed solution is 50 to 60° C., and the reaction time is 2 to 3 hours.
[0014] Specifically, the stirring and mixing time may be any one of 30 min, 35 min, 38 min, 40 min, 45 min, 47 min, 50 min, 55 min, 58 min, and 60 min.
[0015] Specifically, the secondary stirring and mixing time can be any one of 20 min, 23 min, 28 min, 30 min, 35 min, 37 min, and 40 min.
[0016] Specifically, the reaction temperature of the first mixed solution can be any one of 50°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, and 60°C.
[0017] Specifically, the reaction time of the first mixed solution is any one of 2h, 2.1h, 2.3h, 2.4h, 2.6h, 2.7h, 2.9h, and 3h.
[0018] Furthermore, in the preparation process of the polymer B, the mass ratio of acrylamide, N,N'-dimethylacrylamide, deionized water, kerosene, the second emulsifier and the initiator is 1.5-1.6:1.0-1.3:5-5.5:5-5.5:0.1-0.5:0.01-0.3.
[0019] Furthermore, the three stirring and mixing times are 30 to 60 minutes, the four stirring and mixing times are 10 to 20 minutes, the reaction temperature of the second mixed solution is 30 to 60° C., and the reaction time is 3 to 6 hours.
[0020] Specifically, the three stirring and mixing times can be any one of 30 min, 35 min, 38 min, 40 min, 45 min, 47 min, 50 min, 55 min, 58 min, and 60 min.
[0021] Specifically, the four stirring and mixing times may be any one of 10 min, 13 min, 14 min, 15 min, 17 min, 19 min, and 20 min.
[0022] Specifically, the reaction temperature of the second mixed solution can be any one of 30°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 40°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 50°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, and 60°C.
[0023] Specifically, the reaction time of the second mixed liquid is any one of 3h, 3.1h, 3.3h, 3.4h, 3.6h, 3.7h, 4.9h, 4h, 4.1h, 4.3h, 4.4h, 4.6h, 4.7h, 4.9h, 5h, 5.1h, 5.3h, 5.4h, 5.6h, 5.7h, 5.9h, and 6h.
[0024] Furthermore, in the preparation process of the polymer C, the mass ratio of acrylamide, N-(2-(allylbromoamino)-2-phenylethyl)heptylamide, deionized water, kerosene, the third emulsifier, and the initiator is 1-1.5:1-1.5:5-5.5:5-5.5:0.1-0.5:0.01-0.3.
[0025] Furthermore, the five stirring and mixing times are 30 to 60 minutes, the six stirring and mixing times are 10 to 20 minutes, the reaction temperature of the third mixed solution is 30 to 60° C., and the reaction time is 3 to 6 hours.
[0026] Specifically, the five stirring and mixing times may be any one of 30 min, 35 min, 38 min, 40 min, 45 min, 47 min, 50 min, 55 min, 58 min, and 60 min.
[0027] Specifically, the six stirring and mixing times may be any one of 10 min, 13 min, 14 min, 15 min, 17 min, 19 min, and 20 min.
[0028] Specifically, the reaction temperature of the third mixed solution can be any one of 30°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 40°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 50°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, and 60°C.
[0029] Specifically, the reaction time of the third mixed liquid is any one of 3h, 3.1h, 3.3h, 3.4h, 3.6h, 3.7h, 4.9h, 4h, 4.1h, 4.3h, 4.4h, 4.6h, 4.7h, 4.9h, 5h, 5.1h, 5.3h, 5.4h, 5.6h, 5.7h, 5.9h, and 6h.
[0030] Furthermore, the mass ratio of the polymer A, polymer B, polymer C and initiator is 1-1.5:1-1.5:1-1.5:0.01-0.3.
[0031] Furthermore, the reaction temperature of the continued stirring reaction is 30 to 60° C., and the continued stirring reaction time is 3 to 6 hours.
[0032] Specifically, the reaction temperature of the continued stirring reaction can be any one of 30°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 40°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 50°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, and 60°C.
[0033] Specifically, the continued stirring reaction time is any one of 3h, 3.1h, 3.3h, 3.4h, 3.6h, 3.7h, 4.9h, 4h, 4.1h, 4.3h, 4.4h, 4.6h, 4.7h, 4.9h, 5h, 5.1h, 5.3h, 5.4h, 5.6h, 5.7h, 5.9h, and 6h.
[0034] Furthermore, the post-processing specific operations include:
[0035] Add a diverting agent to the obtained polymer D, stir for 1 to 2 hours, filter and take out the filter cake, and dry it to obtain a modified thickener.
[0036] Furthermore, the added mass of the diverting agent is 1-5% of the mass of the obtained polymer D.
[0037] Furthermore, the diverting agent is one or more of alkylphenol polyoxyethylene ether, rock salt, calcium chloride, borax, aminosulfonic acid, trioxymethylene, benzoic acid, and methyl cellulose.
[0038] Furthermore, the molecular weight of the modified thickener is 6 to 8 million.
[0039] The second object of the present invention is to provide a method for preparing a modified thickener, the preparation method comprising:
[0040] Acrylamide, 2-acrylamido-2-methylpropanesulfonic acid and deionized water are prepared into a first aqueous phase solution, kerosene and a first emulsifier are added under nitrogen atmosphere and stirring, and an initiator is added after stirring and mixing once, and stirring and mixing a second time to obtain a first mixed solution, and the obtained first mixed solution is heated to react to obtain a polymer A;
[0041] Acrylamide, N,N'-dimethylacrylamide and deionized water are prepared into a second aqueous phase solution, kerosene and a second emulsifier are added under nitrogen atmosphere and stirring, and the mixture is stirred and mixed three times, and then an initiator is added, and the mixture is stirred and mixed three times to obtain a second mixed solution, and the obtained second mixed solution is heated for reaction to obtain polymer B;
[0042] Acrylamide, N-(2-(allylbromoamino)-2-phenylethyl)heptylamide and deionized water are prepared into a third aqueous phase solution, kerosene and a third emulsifier are added under nitrogen atmosphere and stirring, and after stirring and mixing for five times, an initiator is added and stirred for six times to obtain a third mixed solution, and the obtained third mixed solution is heated for reaction to obtain a polymer C;
[0043] After polymer A, polymer B and polymer C are mixed, they are heated to the reaction temperature under nitrogen atmosphere and stirring, and an initiator is added. The stirring reaction is continued to obtain a product, which is polymer D. After post-treatment, a modified thickener is obtained.
[0044] The third object of the present invention is to provide a gelled acid system, which comprises a modified thickener, an acid solution, a corrosion inhibitor and an iron ion stabilizer, and comprises, by mass percentage, 18-23% of the acid solution, 3-4% of the modified thickener, 1-4% of the corrosion inhibitor, 0.1-0.3% of the iron ion stabilizer, and the balance is water.
[0045] Specifically, the gelled acid system includes, by mass percentage, 20% hydrochloric acid (mass fraction is 37%), 3.5% modified thickener, 1.5% corrosion inhibitor, 0.1% iron ion stabilizer, and the balance is water.
[0046] The mass percentage of the acid solution can also be any one of 18%, 19%, 21%, 22%, and 23%, and the acid solution is hydrochloric acid, earth acid, or a mixture of the two in any ratio. Specifically, the mass fractions of hydrochloric acid and earth acid can be commonly used mass fractions.
[0047] The mass percentage of the modified thickener can also be any one of 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.6%, 3.7%, 3.8%, 3.9%, and 4%;
[0048] The mass percentage of the corrosion inhibitor can also be any one of 1%, 1.3%, 1.8%, 2%, 2.4%, 2.5%, 2.9%, 3%, 3.2%, 3.5%, 3.7%, 3.9%, and 4%;
[0049] The mass percentage of the iron ion stabilizer can also be any one of 0.12%, 0.14%, 0.17%, 0.2%, 0.23%, 0.26%, 0.28%, 0.29%, and 0.3%.
[0050] Specifically, during actual use, the mass fractions of hydrochloric acid and mud acid in the acid solution are adjusted according to the reservoir properties.
[0051] Furthermore, the corrosion inhibitor is a Mannich base corrosion inhibitor, mainly a Mannich base quaternary ammonium salt corrosion inhibitor. Referring to CN115043822A, it can effectively reduce the corrosion problem of acid solution in the gelled acid system on the wellbore and downhole tools. Compared with other types of corrosion inhibitors, Mannich base quaternary ammonium salt corrosion inhibitors have better corrosion inhibition performance in acid solution, especially after the Mannich base is quaternized, not only the molecule is larger, but also contains N + , with better corrosion inhibition performance. In addition, due to the generation of quaternary ammonium salts and hydrophilic groups in the molecules, the acid solubility of the corrosion inhibitor is greatly improved, so it can have better compatibility with the gelled acid system.
[0052] Furthermore, the iron ion stabilizer is one of ammonium chloride, trisodium phosphate, sodium succinate, or a mixture of any ratio of the two or more thereof.
[0053] Furthermore, the gelled acid system can withstand a high temperature of 200°C. After the gelled acid system is sheared at 200°C for 2h, the viscosity of the gelled acid system is greater than 18mPa·s, and the corrosion rate is less than 80g / m2·h. It is suitable for reservoir conditions of 80 to 230°C and can be used for high-temperature reservoir reconstruction of deep wells, ultra-deep wells, etc.
[0054] Beneficial effects of the present invention:
[0055] The modified thickener of the present invention is a gelling acid system main agent, which is copolymerized by acrylamide (AM), 2-acrylamido-2-methylpropanesulfonic acid (AMPS), N,N'-dimethylacrylamide (DMAM), N-(2-(allyl bromide amino)-2-phenylethyl) heptylamide, etc. by a step-by-step reverse emulsion polymerization method. Compared with conventional polyacrylamide synthesis, the step-by-step reverse emulsion polymerization method mostly adopts ternary copolymerization, and quaternary copolymerization is more difficult and has a lower yield, thereby improving the yield of the synthesized polyacrylamide and reducing the difficulty of synthesis. The molecular weight of the modified thickener is 6 to 8 million, and the gelling acid body formed by the combination thereof can realize self-degradation without adding a degrading agent, compared with a conventional slippery water system, has no micelles after degrading, and has a low residue content;
[0056] The modified thickener can be scientifically compatible with other components in the gelled acid system, so that the obtained gelled acid system has acid resistance compared with conventional fracturing fluid systems, can withstand acid solutions such as hydrochloric acid and mud acid, does not precipitate or hydrolyze, and maintains stable viscosity;
[0057] The gelled acid system provided by the present invention realizes the high temperature resistance of the gelled acid system at 200°C, can withstand various acid systems such as hydrochloric acid and earth acid, and does not precipitate or degrade. The system is equipped with a corrosion inhibitor system with good compatibility, has no precipitation, and can effectively reduce corrosion to the wellbore and downhole equipment. For carbonate rock systems, the gelled acid system provided by the present invention can form effective dissolution, act on the deep part of the shale oil reservoir, improve the reservoir porosity and permeability, and has good reservoir transformation ability.
[0058] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0060] Figure 1 A picture of a steel sheet before corrosion in a gelled acid system according to an embodiment of the present invention is shown;
[0061] Figure 2 A picture of a steel sheet after being corroded by a gelled acid system for 4 hours according to an embodiment of the present invention is shown;
[0062] Figure 3 A state diagram of a gel-breaking liquid of a gelling acid system according to an embodiment of the present invention is shown;
[0063] Figure 4 A temperature resistance and shear resistance performance curve diagram according to an embodiment of the present invention is shown. DETAILED DESCRIPTION
[0064] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0065] Example 1
[0066] Preparation of modified thickener:
[0067] Step A1, acrylamide, 2-acrylamide-2-methylpropane sulfonic acid and deionized water are prepared into a first aqueous phase solution, kerosene and Span80 are added under nitrogen atmosphere and stirring, azobisisobutyronitrile is added after stirring and mixing once, azobisisobutyronitrile is added, stirring and mixing twice to obtain a first mixed solution, the obtained first mixed solution is heated to react to obtain polymer A, the first stirring and mixing time is 30 minutes, the second stirring and mixing time is 40 minutes, the reaction temperature of the first mixed solution is 50°C, the reaction time is 2 hours, and the acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, deionized water, kerosene, Span80, and azobisisobutyronitrile are added according to the mass parts of 10 parts: 10 parts: 70 parts: 4 parts: 2 parts: 1 part;
[0068] Step A2, acrylamide, N, N'-dimethylacrylamide and deionized water are prepared into a second aqueous phase solution, kerosene and Tween80 are added under nitrogen atmosphere and stirring, and after stirring and mixing three times, azobisisobutyronitrile is added, and stirring and mixing is performed four times to obtain a second mixed solution, and the obtained second mixed solution is heated to react to obtain polymer B; the three stirring and mixing time is 35 minutes, the four stirring and mixing time is 10 minutes, the reaction temperature of the second mixed solution is 30°C, and the reaction time is 6 hours, and the acrylamide, N, N'-dimethylacrylamide, deionized water, kerosene, Tween80, and azobisisobutyronitrile are added according to the mass parts of 15 parts: 10 parts: 50 parts: 50 parts: 4 parts: 1 part;
[0069] Step A3, acrylamide, N-(2-(allyl bromide amino)-2-phenylethyl) heptylamide and deionized water are prepared into a third aqueous phase solution, kerosene and Tween80 are added under nitrogen atmosphere and stirring, after five times of stirring and mixing, azobisisobutyronitrile is added, and the mixture is stirred for six times to obtain a third mixed solution, and the obtained third mixed solution is heated to react to obtain polymer C, wherein the five stirring and mixing time is 40 min, the six stirring and mixing time is 20 min, the reaction temperature of the third mixed solution is 30° C., and the reaction time is 6 h; the acrylamide, N-(2-(allyl bromide amino)-2-phenylethyl) heptylamide, deionized water, kerosene, Tween80, and azobisisobutyronitrile are fed in the ratio of 10 parts: 10 parts: 50 parts: 50 parts: 4 parts: 1 part by mass;
[0070] Step A4, after polymer A, polymer B and polymer C are mixed, heated to the reaction temperature under nitrogen atmosphere and stirring, and azobisisobutyronitrile is added, and the reaction is continued with stirring to obtain a product as polymer D, and 1% alkylphenol polyoxyethylene ether by mass of polymer D is added to the obtained polymer D, and stirred for 1 hour, the filter cake is filtered and dried to obtain a modified thickener, and a modified thickener is obtained; the reaction temperature is 30° C., and the stirring reaction time is continued for 6 hours. The polymer A, polymer B, polymer C, and azobisisobutyronitrile are added according to the mass parts of 10:10:10:0.1 parts.
[0071] It is measured that the molecular weight of the modified thickener is 6 to 8 million.
[0072] Example 2
[0073] Preparation of modified thickener:
[0074] Step A1, acrylamide, 2-acrylamide-2-methylpropane sulfonic acid and deionized water are prepared into a first aqueous phase solution, kerosene and Span20 are added under nitrogen atmosphere and stirring, azobisisobutyronitrile is added after stirring and mixing once, azobisisobutyronitrile is added, stirring and mixing twice to obtain a first mixed solution, the obtained first mixed solution is heated to react to obtain polymer A, the first stirring and mixing time is 40 minutes, the second stirring and mixing time is 230 minutes, the reaction temperature of the first mixed solution is 60°C, the reaction time is 2.5 hours, and the acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, deionized water, kerosene, Span20, and azobisisobutyronitrile are added according to the weight parts of 10 parts: 12 parts: 75 parts: 4 parts: 1.5 parts: 0.5 parts;
[0075] Step A2, acrylamide, N, N'-dimethylacrylamide and deionized water are prepared into a second aqueous phase solution, kerosene and Span80 are added under nitrogen atmosphere and stirring, and after stirring and mixing three times, azobisisobutyronitrile is added, and stirred and mixed four times to obtain a second mixed solution, and the obtained second mixed solution is heated to react to obtain polymer B; the three stirring and mixing time is 30 minutes, the four stirring and mixing time is 20 minutes, the reaction temperature of the second mixed solution is 40°C, and the reaction time is 4 hours, and the acrylamide, N, N'-dimethylacrylamide, deionized water, kerosene, Span80, and azobisisobutyronitrile are added according to the mass parts of 17 parts: 11 parts: 53 parts: 50 parts: 4 parts: 1 part;
[0076] Step A3, acrylamide, N-(2-(allyl bromide amino)-2-phenylethyl) heptylamide and deionized water are prepared into a third aqueous phase solution, kerosene and Tween80 are added under nitrogen atmosphere and stirring, after five times of stirring and mixing, azobisisobutyronitrile is added, and the mixture is stirred for six times to obtain a third mixed solution, and the obtained third mixed solution is heated to react to obtain polymer C, wherein the five stirring and mixing time is 45 min, the six stirring and mixing time is 15 min, the reaction temperature of the third mixed solution is 50° C., and the reaction time is 4 h; the acrylamide, N-(2-(allyl bromide amino)-2-phenylethyl) heptylamide, deionized water, kerosene, Tween80, and azobisisobutyronitrile are fed in the proportion of 12 parts: 10 parts: 53 parts: 50 parts: 3 parts: 1 part by mass;
[0077] Step A4, after polymer A, polymer B and polymer C are mixed, heated to the reaction temperature under nitrogen atmosphere and stirring, and azobisisobutyronitrile is added, and the reaction is continued with stirring to obtain a product as polymer D, and 2% of alkylphenol polyoxyethylene ether by weight of polymer D is added to the obtained product, stirred for 1 to 2 hours, filtered to obtain the filter cake, and dried to obtain a modified thickener, and a modified thickener is obtained; the polymer A, polymer B, polymer C, and azobisisobutyronitrile are added according to the weight parts of 12:14:10:0.3 parts.
[0078] It is measured that the molecular weight of the modified thickener is 6 to 8 million.
[0079] Example 3
[0080] Preparation of modified thickener:
[0081] Step A1, acrylamide, 2-acrylamide-2-methylpropane sulfonic acid and deionized water are prepared into a first aqueous phase solution, kerosene and Tween80 are added under nitrogen atmosphere and stirring, azobisisobutyronitrile is added after stirring and mixing once, azobisisobutyronitrile is added, stirring and mixing twice to obtain a first mixed solution, the obtained first mixed solution is heated to react to obtain polymer A, the first stirring and mixing time is 60 minutes, the second stirring and mixing time is 20 minutes, the reaction temperature of the first mixed solution is 60°C, the reaction time is 2 hours, and the acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, deionized water, kerosene, Tween80, and azobisisobutyronitrile are added according to the mass parts of 10 parts: 10 parts: 70 parts: 4 parts: 2 parts: 1 part;
[0082] Step A2, acrylamide, N, N'-dimethylacrylamide and deionized water are prepared into a second aqueous phase solution, kerosene and Span80 are added under nitrogen atmosphere and stirring, and after stirring and mixing three times, azobisisobutyronitrile is added, and stirred and mixed four times to obtain a second mixed solution, and the obtained second mixed solution is heated to react to obtain polymer B; the three stirring and mixing time is 60 minutes, the four stirring and mixing time is 15 minutes, the reaction temperature of the second mixed solution is 60°C, and the reaction time is 3 hours, and the acrylamide, N, N'-dimethylacrylamide, deionized water, kerosene, Span80, and azobisisobutyronitrile are added according to the mass parts of 15 parts: 10 parts: 53 parts: 50 parts: 3 parts: 1 part;
[0083] Step A3, acrylamide, N-(2-(allyl bromide amino)-2-phenylethyl) heptylamide and deionized water are prepared into a third aqueous phase solution, kerosene and Span80 are added under nitrogen atmosphere and stirring, after five times of stirring and mixing, azobisisobutyronitrile is added, and the mixture is stirred for six times to obtain a third mixed solution, and the obtained third mixed solution is heated to react to obtain polymer C, wherein the five stirring and mixing time is 50 min, the six stirring and mixing time is 20 min, the reaction temperature of the third mixed solution is 60° C., and the reaction time is 3 h; the acrylamide, N-(2-(allyl bromide amino)-2-phenylethyl) heptylamide, deionized water, kerosene, Span80, and azobisisobutyronitrile are added in the proportion of 10 parts: 13 parts: 53 parts: 50 parts: 3 parts: 1 part by mass;
[0084] Step A4, after polymer A, polymer B and polymer C are mixed, heated to the reaction temperature under nitrogen atmosphere and stirring, and azobisisobutyronitrile is added, and the reaction is continued with stirring to obtain a product as polymer D, and 5% of the mass of polymer D alkylphenol polyoxyethylene ether is added to the obtained polymer D, and stirred for 2 hours, and the filter cake is filtered and dried to obtain a modified thickener, and a modified thickener is obtained; the reaction temperature is 60°C, and the stirring reaction time is continued for 3 hours. The polymer A, polymer B, polymer C, and azobisisobutyronitrile are added according to the mass parts of 12:12:11:0.2 parts.
[0085] It is measured that the molecular weight of the modified thickener is 6 to 8 million.
[0086] The modified thickener obtained in Examples 1-3 was mixed with an acid solution, a corrosion inhibitor and an iron ion stabilizer according to Table 1 to prepare a gelled acid system.
[0087] Table 1
[0088]
[0089]
[0090] Among them, the corrosion inhibitor is an integrated corrosion inhibitor and drainage aid, including a Mannich base corrosion inhibitor (see patent CN115043822A benzotriazole derivatives and their preparation methods, benzotriazole corrosion inhibitors and their applications) mixed with methanol or ethylene glycol in a mass ratio of 10:90; the iron ion stabilizer is sodium acetate.
[0091] Example 4
[0092] The gelled acid system 1 was used to measure the static corrosion rates of P110 steel sheet and N80 steel sheet at normal pressure according to step 5.1 in SY / T 5405-2019 "Performance Experimental Methods and Evaluation Indicators of Corrosion Inhibitors for Acidification".
[0093] The condition of the steel sheet before and after 4 hours of corrosion is as follows Figure 1-Figure 2 As shown, Figure 1 and Figure 2 The first and third steel sheets in the middle are P110 steel sheets, and the second and fourth steel sheets in the middle are N80 steel sheets;
[0094] The corrosion rate results are shown in Table 2. The corrosion rate of P110 steel sheet is 5.87 g / (m 2 ·h), the corrosion rate of N80 steel sheet is 15.29g / (m 2 ·h), it can be seen that the ultra-high temperature gelled acid system has a strong corrosion inhibition ability.
[0095] Table 2
[0096]
[0097] Example 5
[0098] The gelled acid system 2 was added to the pressure vessel and placed in an oven at 200°C for 4 h. The viscosity of the degelling fluid was measured using a Haake rheometer. The residue content was measured according to step 7.10 of "SY / T 5107-2016 Performance Evaluation Method for Water-Based Fracturing Fluid".
[0099] The results are as follows Figure 3 As shown in Figure 1, the viscosity of the gelling liquid of the gelling acid system 1 is 1.76 mPa·s, and the residual content of the gelling liquid is 9.6 mg·L -1 , indicating that the gel breaking performance is good.
[0100] Example 6
[0101] Use Haake rheometer at 200℃, 100s -1 The temperature and shear resistance of gelled acid system 3 was measured after shearing for 120 minutes.
[0102] The results are as follows Figure 4 As shown, the final viscosity of the ultra-high temperature gelled acid system is greater than 18 mPa·s, indicating that it has certain temperature and shear resistance.
[0103] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A modified thickener, characterized in that: The method comprises the following steps: Acrylamide, 2-acrylamido-2-methylpropanesulfonic acid and deionized water are prepared into a first aqueous phase solution, kerosene and a first emulsifier are added under nitrogen atmosphere and stirring, and an initiator is added after stirring and mixing once, and stirring and mixing a second time to obtain a first mixed solution, and the obtained first mixed solution is heated to react to obtain a polymer A; Acrylamide, N,N'-dimethylacrylamide and deionized water are prepared into a second aqueous phase solution, kerosene and a second emulsifier are added under nitrogen atmosphere and stirring, and the mixture is stirred and mixed three times, and then an initiator is added, and the mixture is stirred and mixed four times to obtain a second mixed solution, and the obtained second mixed solution is heated to react to obtain polymer B; Acrylamide, N-(2-(allylbromoamino)-2-phenylethyl)heptylamide and deionized water are prepared into a third aqueous phase solution, kerosene and a third emulsifier are added under nitrogen atmosphere and stirring, and after stirring and mixing for five times, an initiator is added and stirred for six times to obtain a third mixed solution, and the obtained third mixed solution is heated for reaction to obtain a polymer C; After polymer A, polymer B and polymer C are mixed, they are heated to the reaction temperature under nitrogen atmosphere and stirring, and an initiator is added. The stirring reaction is continued to obtain a product, which is polymer D. After post-treatment, a modified thickener is obtained.
2. The modified thickener according to claim 1, characterized in that: During the preparation of the polymer A, the mass ratio of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, deionized water, kerosene, the first emulsifier, and the initiator is 1-1.5:1-1.5:7-7.5:4-4.5:0.1-0.5:0.01-0.
3.
3. The modified thickener according to claim 1, characterized in that: The first stirring and mixing time is 30 to 60 minutes, the second stirring and mixing time is 20 to 40 minutes, the reaction temperature of the first mixed solution is 50 to 60° C., and the reaction time is 2 to 3 hours.
4. The modified thickener according to claim 1, characterized in that: During the preparation of the polymer B, the mass ratio of acrylamide, N,N'-dimethylacrylamide, deionized water, kerosene, the second emulsifier and the initiator is 1.5-1.6:1.0-1.3:5-5.5:5-5.5:0.1-0.5:0.01-0.
3.
5. The modified thickener according to claim 1, characterized in that: The three stirring and mixing times are 30 to 60 minutes, the four stirring and mixing times are 10 to 20 minutes, the reaction temperature of the second mixed solution is 30 to 60° C., and the reaction time is 3 to 6 hours.
6. The modified thickener according to claim 1, characterized in that: In the preparation process of the polymer C, the mass ratio of acrylamide, N-(2-(allylbromoamino)-2-phenylethyl)heptylamide, deionized water, kerosene, the third emulsifier and the initiator is 1-1.5:1-1.5:5-5.5:5-5.5:0.1-0.5:0.01-0.
3.
7. The modified thickener according to claim 1, characterized in that: The five stirring and mixing times are 30 to 60 minutes, the six stirring and mixing times are 10 to 20 minutes, the reaction temperature of the third mixed solution is 30 to 60° C., and the reaction time is 3 to 6 hours.
8. The modified thickener according to claim 1, characterized in that: The mass ratio of the polymer A, polymer B, polymer C and initiator is 1-1.5:1-1.5:1-1.5:0.01-0.
3.
9. The modified thickener according to claim 1, characterized in that: The reaction temperature of the continued stirring reaction is 30-60° C., and the continued stirring reaction time is 3-6 hours.
10. The modified thickener according to claim 1, characterized in that: The specific post-processing operations include: Add a diverting agent to the obtained polymer D, stir for 1 to 2 hours, filter and take out the filter cake, and dry it to obtain a modified thickener.
11. The modified thickener according to claim 10, characterized in that: The added mass of the diverting agent is 1-5% of the mass of the obtained polymer D.
12. The modified thickener according to any one of claims 1 to 11, characterized in that: The molecular weight of the modified thickener is 6 to 8 million.
13. A method for preparing a modified thickener, characterized in that: include: Acrylamide, 2-acrylamido-2-methylpropanesulfonic acid and deionized water are prepared into a first aqueous phase solution, kerosene and a first emulsifier are added under nitrogen atmosphere and stirring, and an initiator is added after stirring and mixing once, and stirring and mixing a second time to obtain a first mixed solution, and the obtained first mixed solution is heated to react to obtain a polymer A; Acrylamide, N,N'-dimethylacrylamide and deionized water are prepared into a second aqueous phase solution, kerosene and a second emulsifier are added under nitrogen atmosphere and stirring, and the mixture is stirred and mixed three times, and then an initiator is added, and the mixture is stirred and mixed three times to obtain a second mixed solution, and the obtained second mixed solution is heated for reaction to obtain polymer B; Acrylamide, N-(2-(allylbromoamino)-2-phenylethyl)heptylamide and deionized water are prepared into a third aqueous phase solution, kerosene and a third emulsifier are added under nitrogen atmosphere and stirring, and after stirring and mixing for five times, an initiator is added and stirred for six times to obtain a third mixed solution, and the obtained third mixed solution is heated for reaction to obtain a polymer C; After polymer A, polymer B and polymer C are mixed, they are heated to the reaction temperature under nitrogen atmosphere and stirring, and an initiator is added. The stirring reaction is continued to obtain a product, which is polymer D. After post-treatment, a modified thickener is obtained.
14. A gelled acid system, characterized in that: The invention comprises the modified thickener according to any one of claims 1 to 12, acid solution, corrosion inhibitor and iron ion stabilizer.
15. A gelled acid system according to claim 14, characterized in that: Calculated by mass percentage, it includes: 18-23% acid solution, 3-4% modified thickener, 1-4% corrosion inhibitor, 0.1-0.3% iron ion stabilizer, and the balance is water.
16. A gelled acid system according to claim 15, characterized in that: After the gelled acid system is sheared at 200° C. for 2 h, the viscosity of the gelled acid system is greater than 18 mPa·s, and the corrosion rate is less than 80 g / m2·h.
Citation Information
Patent Citations
Benzotriazole derivative, preparation method of benzotriazole derivative, benzotriazole corrosion inhibitor and application of benzotriazole corrosion inhibitor
CN115043822A